The human body and weightlessness : operational effects, problems and countermeasures - Thornton, William ; Bonato, Frederick (Springer, 2020)
This book focuses on all of the major problems associated with the absence of body weight in space, by analyzing effects, adaption, and re-adaptation upon returning to Earth, using sound scientific principles embedded in a historical context. Serious problems for space travelers range from Space Motion Sickness (SMS) to recently discovered ocular effects that may permanently impair vision. Fluid loss and shifts, spinal changes, and bone and muscle loss are also all results of weightlessness. Starting with a brief definition and history of weightlessness, the authors then address in detail each problem as well as the countermeasures aimed at alleviating them. In some cases, alternative hypotheses regarding what can and should be attempted are also presented. As plans for long-term missions to the Moon and Mars develop, it will be essential to find countermeasures to weightlessness that are effective for missions that could span years.